Educational technology in secondary agricultural education programs: a national study - Jeffery, Terrel W., author; Whaley, David C., advisor; Lewis, Wiley B., committee member; Jansen, Duane, committee member; Johnson, Russell, committee member (Colorado State University. Libraries, 1999)
The purpose of this study was to assess the extent of the use of technology in secondary agricultural education programs in the United States. Comparison with a 1989 study by Birkenholz, Stewart, and Craven provided the basis for determining the increase or decrease of the use of technology in the classroom over the past ten years. A survey was employed similar to the one used in this 1989 study, requesting information about the type and quantity of equipment in inventory, level of current and anticipated use, future needs, what data was used from informational services, what educational and curriculum materials were valued, and whether technology had been adopted as a pedagogy was sent to 373 randomly selected secondary agricultural teachers. Usable data were compiled from 183 teachers, a 49% response rate. The study showed the following findings: the use of microcomputers in the agricultural classroom has significantly increased, from 73% in 1989 to 98% in 1999. Apple was the dominant system in 1989 at 64%; in 1999 the Personal Computer (MS-DOS) is used in 73% of the programs. The use of an Internet service provider by agricultural education programs has increased 31%, the current and anticipated use of technology has increased 50%, a word processing program is the software most often used. Lesson plans remain the most preferred feature of a computer accessed database information system. Lack of funds remains the most often cited barrier to the utilization of educational technology. More teachers have incorporated the use of technology in their curriculum. This researcher recommends that agricultural educators identify ways to overcome the barriers of limited funds which restrict the utilization of the new technologies. The lack of expertise is not as much a barrier in 1999 as it was in 1989; however, continued inservice is essential to the improved use of technology. A continued increase in the use of technology in preparing the agricultural education students for their future employment is seriously recommended.
Keywords: vocational education; agricultural education; educational technology